Platinum-nickel loaded molybdenum carbide / molybdenum dioxide nano composite material, preparation method and application
By loading PtNi alloy on Mo2C/MoO2 substrate material, a platinum nickel-loaded molybdenum carbide/molybdenum dioxide nanocomposite was formed, which solved the problem of poor performance of existing catalysts under acidic conditions, and achieved efficient and stable electrocatalytic hydrogen evolution performance and reduce costs.
Patent Information
- Application Number
- CN202411528155.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Existing HER catalysts perform poorly under acidic conditions, especially in terms of long-term durability, and high Pt content leads to high costs and is difficult to apply on a large scale.
The nanocomposite material of platinum nickel-loaded molybdenum carbide/molybdenum dioxide is used to improve catalytic activity and stability by loading PtNi alloy on the Mo2C/MoO2 substrate material.
Under acidic conditions, the electrocatalytic hydrogen evolution performance and stability are significantly improved, and the use of precious metal Pt is reduced, which is cost-effective and suitable for industrial applications.
Smart Images

Figure CN119392295A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic hydrogen evolution catalytic materials, and particularly relates to a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material, a preparation method and an application thereof. Background Art
[0002] Hydrogen (H2) has attracted widespread attention due to its environmental friendliness, high calorific value and power density. The raw materials for hydrogen production by water electrolysis are abundant. The production of high-purity hydrogen by using electricity generated from renewable energy is simple, efficient and easy to promote. It is a sustainable, green and environmentally friendly approach. The hydrogen evolution reaction (HER) is an important step in the preparation of high-purity hydrogen. However, its development is hindered by high energy consumption and slow kinetics. It is important to design efficient electrocatalysts to improve the kinetics of the catalytic reaction. Most of the currently developed HER catalysts perform well under alkaline conditions, but poorly under acidic conditions, especially long-term durability.
[0003] As the most advanced HER catalyst, Pt-based precious metal materials cannot be used on a large scale due to their small Pt reserves and high prices. Therefore, it is of great significance to develop low Pt-loaded electrocatalysts with high intrinsic catalytic activity.
[0004] Loading Pt on a suitable carrier is an ideal way to reduce costs. It can not only effectively reduce the Pt content, but also avoid the agglomeration of Pt nanoparticles. The properties of the carrier play an important role in the activity and stability of the catalyst. Therefore, choosing a suitable carrier is critical. Studies have found that transition metal oxides and carbides (such as MoO2, Mo2C) have their unique electronic structures and have superior activity and stability for HER. However, low catalytic efficiency or poor stability leads to unsatisfactory hydrogen evolution performance of single-phase MoO2 and Mo2C. The intrinsic catalytic performance can be enhanced by optimizing the electronic structure of the active site using a heterostructure coupling strategy. The heterogeneous interface formed between the two components can optimize the electronic structure, and the electronic coupling and interfacial synergistic effects can enhance the reactivity of the active site. Although this type of catalyst has excellent catalytic activity, its activity is not enough for industrial applications, especially the stability at high current density under acidic conditions. Therefore, it is necessary to find a simple and low-cost method to obtain heterogeneous interface materials with trace Pt loads and apply them to catalytic electrolysis of water for hydrogen evolution under acidic high current density. This will provide more scientific basis and technical support for the development and application of hydrogen production technology by electrolysis of water. Summary of the invention
[0005] In view of the problems existing in the background technology, the purpose of the present invention is to provide a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material, a preparation method and an application thereof. The raw materials used in the preparation method are cheap, the process and equipment are simple, the production cost is low, and large-scale production is easy to achieve. The obtained platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material has excellent electrocatalytic performance.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a platinum-nickel-loaded molybdenum carbide / molybdenum dioxide nanocomposite material, comprising the following steps:
[0008] S1. Preparation of Mo2C / MoO2 substrate material containing heterojunction:
[0009] S11, dissolving the metal molybdenum salt and the ligand in deionized water, adjusting the pH to 4-5, reacting at a certain temperature, purifying, and drying;
[0010] S12, subjecting the dried reaction product to pyrolysis treatment to obtain a Mo2C / MoO2 substrate material containing a heterojunction as a carrier;
[0011] S2. Preparation of platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite materials:
[0012] The Mo2C / MoO2 substrate material containing the heterojunction is dissolved in water, and a platinum source, a nickel source, a surfactant, a reducing solvent and an acid are added, mixed and reacted to obtain a platinum-nickel-loaded molybdenum carbide / molybdenum dioxide nanocomposite material, hereinafter abbreviated as PtNi-Mo2C / MoO2 composite material.
[0013] Preferably, in step S11, the ratio of the amount of the metal molybdenum salt, the complexing agent and the deionized water is 2-5 g: 1-3 mL: 25-40 mL.
[0014] Preferably, in step S11, the reaction temperature is 30-80° C., and the reaction time is 2-3 h.
[0015] Preferably, in step S11, the purification includes: filtering and washing the reaction product, wherein the filtering method is vacuum filtration, and the washing is performed by washing with water and ethanol in sequence.
[0016] Preferably, in step S11, the drying temperature is 30-100°C.
[0017] Preferably, in step S12, the pyrolysis treatment is at 600-650° C. and the pyrolysis time is 1-2 hours.
[0018] Preferably, in step S2, the reaction temperature is 50-90° C., and the reaction time is 5-10 h.
[0019] Preferably, in step S2, the platinum source, nickel source, surfactant, Mo2C / MoO2 substrate material containing a heterojunction, reducing solvent, acid and deionized water are used in a ratio of 5-35 mg: 5-35 mg; 30-50 mg: 100 mg: 10 μL: 25 μL: 20 mL.
[0020] Preferably, in step S1, the acid for adjusting pH is any one of dilute hydrochloric acid, dilute sulfuric acid, and acetic acid, more preferably dilute hydrochloric acid, with a concentration of 1 to 5 mol / L.
[0021] Preferably, in step S1, the metal molybdenum salt is ammonium heptamolybdate tetrahydrate; and the complexing agent is ethylenediamine.
[0022] Preferably, in step S2, the platinum source is potassium chloroplatinate; the acid is hydrochloric acid with a concentration of 6 to 10 mol / L; the nickel source is nickel chloride hexahydrate; the surfactant is polyoxyethylene polyoxypropylene ether; and the reducing solvent is ethanol.
[0023] The second aspect of the present invention is to provide a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material prepared by the above preparation method.
[0024] Preferably, the Mo2C / MoO2 substrate material containing the heterojunction is a nanorod structure.
[0025] Preferably, the platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material is a nanorod-like structure.
[0026] Preferably, the platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material is a nanorod with a diameter of 100-200 nm, which is composed of platinum-nickel alloy particles with an average size of 3-10 nm uniformly distributed on the Mo2C / MoO2 nanorods.
[0027] Preferably, the content of Pt in the platinum-nickel supported molybdenum carbide / molybdenum dioxide nanocomposite material is less than 1 wt %.
[0028] The third aspect of the present invention is to provide the use of the above-mentioned platinum-nickel supported molybdenum carbide / molybdenum dioxide nanocomposite material as a catalyst in the catalytic hydrogen evolution in water electrolysis.
[0029] The present invention has the following beneficial effects:
[0030] (1) The present invention first uses metal molybdenum salt and coordination agent as raw materials to prepare Mo2C / MoO2 substrate material containing heterojunction, and then loads PtNi on the Mo2C / MoO2 substrate material to prepare platinum nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material. Among them, the MoO2 / Mo2C substrate material as a carrier can well anchor the PtNi alloy, which can further improve the catalytic stability of the material, and the generation of heterojunction in the molybdenum carbide / molybdenum dioxide (Mo2C / MoO2) substrate material, the electronic coupling and interface synergistic effect provided by its heterogeneous interface can enhance the reactivity of the active site, which is conducive to maximizing the performance of the material, while reducing the cost, and further reducing the cost of hydrogen production application under acidic conditions. The experimental results show that the use of the platinum nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material can minimize the use of precious metal Pt, and exhibit excellent electrocatalytic hydrogen evolution performance and stability under acidic (0.5M H2SO4) conditions.
[0031] (2) The preparation method of the present invention has the characteristics of cheap raw materials, simple and easy operation of the process and equipment, low production cost, and easy large-scale industrial production, so it has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 XRD patterns of the PtNi-Mo2C / MoO2 composite material and the Mo2C / MoO2 substrate material containing a heterojunction prepared in Example 1;
[0034] Figure 2 SEM images of different regions of the Mo2C / MoO2 substrate material containing heterojunction: (a) scale bar is 1 μm; (b) scale bar is 1 μm;
[0035] Figure 3 The SEM images of different regions of the PtNi-Mo2C / MoO2 composite material prepared in Example 1 are as follows: (a) scale is 1 μm, (b) scale is 1 μm;
[0036] Figure 4TEM and element distribution diagram of the PtNi-Mo2C / MoO2 composite material prepared in Example 1: (a) TEM diagram with a scale of 100 nm, (b) TEM diagram with a scale of 20 nm, (c) TEM diagram with a scale of 5 nm, and (dh) element distribution diagram with a scale of 50 nm;
[0037] Figure 5 This is the XPS graph of the PtNi-Mo2C / MoO2 composite material prepared in Example 1;
[0038] Figure 6 Electrochemical performance diagrams of the PtNi-Mo2C / MoO2 composite material and the Mo2C / MoO2 substrate material containing a heterojunction in 0.5M H2SO4 prepared in Example 1: (a) LSV diagram of the PtNi-Mo2C / MoO2 composite material and the Mo2C / MoO2 substrate material in 0.5M H2SO4; (b) overpotential and Tafel slope diagram of the PtNi-Mo2C / MoO2 composite material and the Mo2C / MoO2 substrate material in 0.5M H2SO4;
[0039] Figure 7 Electrochemical performance diagrams of PtNi-Mo2C / MoO2 composite materials, Pt-Mo2C / MoO2 composite materials and Ni-Mo2C / MoO2 composite materials in 0.5M H2SO4 prepared in Example 1 and Comparative Examples 1-2: (a) LSV diagram of PtNi-Mo2C / MoO2 composite materials, Pt-Mo2C / MoO2 composite materials and Ni-Mo2C / MoO2 composite materials in 0.5M H2SO4; (b) LSV diagram of PtNi-Mo2C / MoO2 composite materials at 1A cm in 0.5M H2SO4 -2 Long-term stability test under current density;
[0040] Figure 8 This is a comparison chart of current density and mass activity of the PtNi-Mo2C / MoO2 composite material prepared in Example 1 and commercial Pt / C in 0.5M H2SO4. DETAILED DESCRIPTION
[0041] In the following description, for the purpose of illustration rather than limitation, specific details such as specific system structures and technologies are provided to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may also be implemented in other embodiments without these specific details.
[0042] Example 1
[0043] A method for preparing a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material comprises the following steps:
[0044] (1) Preparation of Mo2C / MoO2 substrate material containing heterojunction as carrier: 2.48g of ammonium heptamolybdate tetrahydrate and 1778μL of ethylenediamine were dissolved in 30mL of distilled water, and then 1mol / L hydrochloric acid adjustment solution was added dropwise to the solution under stirring to adjust the pH value to 4. During the adjustment process, a white precipitate gradually precipitated, and then the adjusted solution was placed in a 50°C water bath and slowly stirred for reaction for 2h. Then, the white precipitate product of the reaction was washed by vacuum filtration. During the washing process, it was first rinsed with 500mL of distilled water and then with 100mL of ethanol. Then, the obtained white precipitate product was dried in an oven at 70°C for 3h. Finally, the dried white precipitate product was placed in a tubular furnace and heated to 650°C for 2h under a 20mL / min argon / hydrogen (hydrogen accounts for 10%) gas flow at a rate of 5°C / min, and then cooled naturally to obtain a Mo2C / MoO2 substrate material containing a heterojunction.
[0045] (2) Platinum-nickel alloy was loaded on a Mo2C / MoO2 substrate material containing a heterojunction to prepare a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material: first, 0.015mmol potassium chloroplatinate, 0.03mmol nickel chloride hexahydrate and 30mg polyoxyethylene polyoxypropylene ether were dissolved in 20mL deionized water, and then 25μL 6M hydrochloric acid, 10μL ethanol and 85mg Mo2C / MoO2 were added, and ultrasonic dispersion was performed for 30min, and then the mixture was placed in a 50℃ water bath with vigorous stirring for 6h, centrifuged to obtain a precipitate, washed with deionized water and anhydrous ethanol several times, and dried at 70℃ for 10h to obtain a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material, recorded as PtNi-Mo2C / MoO2 composite material.
[0046] Example 2
[0047] A method for preparing a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material comprises the following steps:
[0048] (1) Preparation of Mo2C / MoO2 substrate material containing heterojunction as carrier: 2.48g of ammonium heptamolybdate tetrahydrate and 1778μL of ethylenediamine were dissolved in 30mL of distilled water, and then 2mol / L hydrochloric acid adjustment solution was added dropwise to the solution under stirring to adjust the pH value to 5. During the adjustment process, a white precipitate gradually precipitated, and then the adjusted solution was placed in a 30°C water bath and slowly stirred for reaction for 2h. Then, the white precipitate product of the reaction was washed by vacuum filtration. During the washing process, it was first rinsed with 500mL of distilled water and then with 100mL of ethanol. Then, the obtained white precipitate product was dried in an oven at 30°C for 3h. Finally, the dried white precipitate product was placed in a tubular furnace and heated to 650°C for 2h under a 20mL / min argon / hydrogen (hydrogen accounts for 10%) gas flow at a rate of 5°C / min, and then cooled naturally to obtain a Mo2C / MoO2 substrate material containing a heterojunction.
[0049] (2) Platinum-nickel alloy was loaded on a Mo2C / MoO2 substrate material containing a heterojunction to prepare a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material: first, 0.015mmol potassium chloroplatinate, 0.03mmol nickel chloride hexahydrate and 30mg polyoxyethylene polyoxypropylene ether were dissolved in 20mL deionized water, and then 25μL 7M hydrochloric acid, 10μL ethanol and 85mg Mo2C / MoO2 substrate material containing a heterojunction were added, and ultrasonic dispersion was performed for 30min, and then the mixture was placed in a 50°C water bath with vigorous stirring for 8h, and the precipitate was obtained by centrifugation. The precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 70°C for 10h to obtain a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material, recorded as PtNi-Mo2C / MoO2 composite material.
[0050] Example 3
[0051] A method for preparing a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material comprises the following steps:
[0052] (1) Preparation of Mo2C / MoO2 substrate material containing heterojunction as carrier: 2.48g of ammonium heptamolybdate tetrahydrate and 1778μL of ethylenediamine were dissolved in 30mL of distilled water, and then 3mol / L hydrochloric acid adjustment solution was added dropwise to the solution under stirring to adjust the pH value to 4. During the adjustment process, a white precipitate gradually precipitated, and then the adjusted solution was placed in a water bath at 80°C and slowly stirred for reaction for 2h. Then, the white precipitate product of the reaction was washed by vacuum filtration. During the washing process, it was first rinsed with 500mL of distilled water and then with 100mL of ethanol. Then, the obtained white precipitate product was dried in an oven at 50°C for 3h. Finally, the dried white precipitate product was placed in a tubular furnace and heated to 650°C for 1h under a 20mL / min argon / hydrogen (hydrogen accounts for 10%) gas flow at a rate of 5°C / min, and then cooled naturally to obtain a Mo2C / MoO2 substrate material containing a heterojunction.
[0053] (2) Platinum-nickel alloy was loaded on a Mo2C / MoO2 substrate material containing a heterojunction to prepare a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material: first, 0.015mmol potassium chloroplatinate, 0.03mmol nickel chloride hexahydrate and 30mg polyoxyethylene polyoxypropylene ether were dissolved in 20mL deionized water, and then 25μL 8M hydrochloric acid, 10μL ethanol and 85mg Mo2C / MoO2 were added, and ultrasonic dispersion was performed for 30min, and then the mixture was placed in a 50℃ water bath with vigorous stirring for 10h, and the precipitate was obtained by centrifugation. The precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 70℃ for 10h to obtain a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material, which was recorded as PtNi-Mo2C / MoO2 composite material.
[0054] Example 4
[0055] A method for preparing a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material comprises the following steps:
[0056] (1) Preparation of Mo2C / MoO2 substrate material containing heterojunction as carrier: 2.48g of ammonium heptamolybdate tetrahydrate and 1778μL of ethylenediamine were dissolved in 30mL of distilled water, and then 4mol / L hydrochloric acid solution was added dropwise to the solution under stirring to adjust the pH value to 4. During the adjustment process, a white precipitate gradually precipitated, and then the adjusted solution was placed in a 50°C water bath and slowly stirred for reaction for 3h. Then, the white precipitate product of the reaction was washed by vacuum filtration. During the washing process, it was first rinsed with 500mL of distilled water and then with 100mL of ethanol. Then, the obtained white precipitate product was dried in an oven at 100°C for 3h. Finally, the dried white precipitate product was placed in a tubular furnace and heated to 650°C for 2h at a rate of 5°C / min under a 20mL / min argon / hydrogen (hydrogen accounts for 10%) gas flow, and then cooled naturally to obtain a Mo2C / MoO2 substrate material containing a heterojunction.
[0057] (2) Platinum-nickel alloy was loaded on a Mo2C / MoO2 substrate material containing a heterojunction to prepare a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material: first, 0.015mmol potassium chloroplatinate, 0.03mmol nickel chloride hexahydrate and 30mg polyoxyethylene polyoxypropylene ether were dissolved in 20mL deionized water, and then 25μL 9M hydrochloric acid, 10μL ethanol and 85mg Mo2C / MoO2 were added, and ultrasonic dispersion was performed for 30min, and then the mixture was placed in a 70℃ water bath with vigorous stirring for 6h, centrifuged to obtain a precipitate, washed with deionized water and anhydrous ethanol several times, and dried at 70℃ for 10h to obtain a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material, recorded as PtNi-Mo2C / MoO2 composite material.
[0058] Example 5
[0059] A method for preparing a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material comprises the following steps:
[0060] (1) Preparation of Mo2C / MoO2 substrate material containing heterojunction as carrier: 2.48g of ammonium heptamolybdate tetrahydrate and 1778μL of ethylenediamine were dissolved in 30mL of distilled water, and then 5mol / L hydrochloric acid adjustment solution was added dropwise to the solution under stirring to adjust the pH value to 4. During the adjustment process, a white precipitate gradually precipitated, and then the adjusted solution was placed in a 50°C water bath and slowly stirred for reaction for 2h. Then, the white precipitate product of the reaction was washed by vacuum filtration. During the washing process, it was first rinsed with 500mL of distilled water and then with 100mL of ethanol. Then, the obtained white precipitate product was dried in an oven at 50°C for 3h. Finally, the dried white precipitate product was placed in a tubular furnace, and heated to 600°C and maintained for 2h under a 20mL / min argon / hydrogen (hydrogen accounts for 10%) gas flow at a rate of 5°C / min, and then cooled naturally to obtain a Mo2C / MoO2 substrate material containing a heterojunction.
[0061] (2) Platinum-nickel alloy was loaded on a Mo2C / MoO2 substrate material containing a heterojunction to prepare a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material: first, 0.015mmol potassium chloroplatinate, 0.03mmol nickel chloride hexahydrate and 30mg polyoxyethylene polyoxypropylene ether were dissolved in 20mL deionized water, and then 25μL 10M hydrochloric acid, 10μL ethanol and 85mg Mo2C / MoO2 were added, and ultrasonic dispersion was performed for 30min, and then the mixture was placed in a 90℃ water bath with vigorous stirring for 6h, centrifuged to obtain a precipitate, washed with deionized water and anhydrous ethanol several times, and dried at 70℃ for 10h to obtain a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material, recorded as PtNi-Mo2C / MoO2 composite material.
[0062] Comparative Example 1
[0063] A method for preparing a platinum-loaded molybdenum carbide / molybdenum dioxide nanocomposite material comprises the following steps:
[0064] (1) Preparation of Mo2C / MoO2 substrate material containing heterojunction as carrier: 2.48g of ammonium heptamolybdate tetrahydrate and 1778μL of ethylenediamine were dissolved in 30mL of distilled water, and then 1M hydrochloric acid was added dropwise to the solution under stirring to adjust the pH value of the solution to about 4-5. A white precipitate gradually precipitated during the adjustment process. Then the adjusted solution was placed in a 50°C water bath and slowly stirred for reaction for 2h. Then the white precipitate product of the reaction was washed by vacuum filtration. During the washing process, it was first rinsed with 500mL of distilled water and then rinsed with 100mL of ethanol. Then the obtained white precipitate product was dried in an oven at 70°C for 3h. Finally, the dried white precipitate product was placed in a tubular furnace, and heated to 650°C for 2 hours at a heating rate of 5°C / min under a 20mL / min argon / hydrogen (hydrogen accounts for 10%) gas flow, and cooled naturally to obtain a Mo2C / MoO2 substrate material containing a heterojunction.
[0065] (2) Platinum was loaded on a Mo2C / MoO2 carrier containing a heterojunction to prepare a platinum-loaded molybdenum carbide / molybdenum dioxide nanocomposite material: First, 0.015mmol potassium chloroplatinate and 30mg polyoxyethylene polyoxypropylene ether were dissolved in 20mL deionized water, and then 25μL 6M hydrochloric acid, 10μL ethanol and 85mg Mo2C / MoO2 were added and ultrasonically dispersed for 30min. Then, it was placed in a 50℃ water bath and stirred vigorously for 6 hours, and then the precipitate was obtained by centrifugation, washed with deionized water and anhydrous ethanol for many times, and dried at 70℃ for 10h to obtain a platinum-loaded molybdenum carbide / molybdenum dioxide nanocomposite material, recorded as Pt-Mo2C / MoO2.
[0066] Comparative Example 2
[0067] A method for preparing a nickel-loaded molybdenum carbide / molybdenum dioxide nanocomposite material comprises the following steps:
[0068] (1) Preparation of Mo2C / MoO2 matrix material containing heterojunction: 2.48g of ammonium heptamolybdate tetrahydrate and 1778μL of ethylenediamine were dissolved in 30mL of distilled water, and then 1mol / L hydrochloric acid was added dropwise to the solution under stirring to adjust the pH value of the solution to about 4-5. A white precipitate gradually precipitated during the adjustment process. Then the adjusted solution was placed in a 50°C water bath and slowly stirred for reaction for 2h. Then the white precipitate product of the reaction was washed by vacuum filtration. During the washing process, it was first rinsed with 500mL of distilled water and then rinsed with 100mL of ethanol. Then the obtained white precipitate product was dried in an oven at 70°C for 3h. Finally, the dried white precipitate product was placed in a tubular furnace, and the temperature was raised to 650°C for 2 hours at a rate of 5°C / min under a 20mL / min argon / hydrogen (hydrogen accounts for 10%) gas flow, and then cooled naturally to obtain a Mo2C / MoO2 matrix material containing a heterojunction.
[0069] (2) Loading nickel on the Mo2C / MoO2 matrix material containing a heterojunction to prepare a nickel-loaded molybdenum carbide / molybdenum dioxide nanocomposite material: first, 0.015mmol potassium chloroplatinate, 0.03mmol nickel chloride hexahydrate and 30mg polyoxyethylene polyoxypropylene ether were dissolved in 20mL deionized water, and then 25μL 6M hydrochloric acid, 10μL ethanol and 85mg Mo2C / MoO2 were added, and ultrasonic dispersion was performed for 30min, and then it was placed in a 50℃ water bath and vigorously stirred for 6h, and then the precipitate was obtained by centrifugation, washed with deionized water and anhydrous ethanol for multiple times, and dried at 70℃ for 10h to obtain a nickel-loaded molybdenum carbide / molybdenum dioxide nanocomposite material, recorded as Ni-Mo2C / MoO2.
[0070] The PtNi-Mo2C / MoO2 composite material prepared in Example 1 and the Mo2C / MoO2 substrate material containing the heterojunction were characterized by XRD. The characterization results are shown in FIG. Figure 1 shown.
[0071] Depend on Figure 1 The results show obvious crystal diffraction peaks, among which the Mo2C / MoO2 substrate material containing heterojunction corresponds to the diffraction peaks of Mo2C (JCPDS no.15-0457) and MoO2 (JCPDS no.32-0676); a weak diffraction peak of PtNi alloy can be observed in the PtNi-Mo2C / MoO2 composite material obtained after loading PtNi alloy, and the intensity of the overall spectrum peak is weak, which is because the content of Pt is low. The Pt content in the PtNi-Mo2C / MoO2 composite material prepared in Example 1 is 0.6wt% through ICP testing, and no diffraction peak of Ni is observed. This result shows that PtNi is loaded on the Mo2C / MoO2 substrate material containing heterojunction in the form of an alloy.
[0072] The PtNi-Mo2C / MoO2 composite material and the Mo2C / MoO2 substrate material containing the heterojunction prepared in Example 1 were characterized, and SEM images, TEM images and XPS spectra were obtained. The specific results are as follows: Figure 2-5 shown.
[0073] Depend on Figure 2 The results show that the Mo2C / MoO2 substrate material containing the heterojunction has a nanorod-like structure as a whole, which is composed of stacked nanoparticles.
[0074] Depend on Figure 3 The results show that the PtNi-Mo2C / MoO2 composite material has a nanorod-like structure, and the overall gap between the nanorods becomes smaller after loading PtNi, which indicates that the PtNi alloy is loaded on the Mo2C / MoO2 substrate material containing a heterojunction.
[0075] Depend on Figure 4 The results show that the Mo2C / MoO2 substrate material containing the heterojunction has a staggered linear structure ( Figure 4 ac), clear lattice fringes can be observed, indicating that the PtNi-Mo2C / MoO2 composite material prepared in Example 1 has good crystallinity. In addition, through the Mapping diagram ( Figure 4 dh) It can be seen that Pt, Ni, Mo, and C elements are evenly distributed, and PtNi alloy mainly exists on the surface of Mo2C / MoO2 substrate material in the form of load.
[0076] Depend on Figure 5 a A peak at 71.6 eV is observed, which is attributed to the metallic Pt of PtNi-Mo2C / MoO2; a peak at 72.67 eV is observed, which is attributed to the oxidized Pt; three obvious peaks in the Mo 2p region are observed, corresponding to Mo3d 5 / 2 and Mo 3d 3 / 2 , located at 228.7, 229.5 and 231.9 eV, attributed to Mo-C ( Figure 4 b); located at 232.9 and 235.8 eV, attributed to Mo-O; the three obvious peaks in the O 1s region correspond to Mo-O bonds, O vacancies and C=O bonds, respectively; due to the low content of Ni, no obvious spectral peaks were measured, which can also be confirmed by the TEM mapping diagram.
[0077] The above characterization data prove that the Mo2C / MoO2 substrate material containing a heterojunction and the PtNi alloy loaded on the Mo2C / MoO2 containing a heterojunction, namely the PtNi-Mo2C / MoO2 composite material, have been successfully prepared.
[0078] Test Example 1
[0079] The PtNi-Mo2C / MoO2 composite material prepared in Example 1, the Mo2C / MoO2 substrate material containing a heterojunction, and the Pt-Mo2C / MoO2 prepared in Comparative Examples 1-2 were 2、 Ni-Mo2C / MoO2 and commercial Pt / C are used as electrocatalysts in the electrolysis of water to produce hydrogen. The specific steps are as follows:
[0080] Preparation of working electrode: 4 mg of electrocatalyst and 80 μL of 5 wt% Nafion solution were dispersed in 1 mL of deionized water / ethanol mixed solution (V / V=4 / 1) to form a uniform catalyst suspension; 5 μL of the suspension was dropped on the surface of a glassy carbon electrode (3 mm in diameter) and dried at room temperature to obtain a working electrode loaded with electrocatalyst.
[0081] The electrocatalytic hydrogen evolution performance test of the catalyst was carried out in a standard three-electrode cell, with a glassy carbon electrode (0.5cm*0.5cm*0.1cm) loaded with the catalyst as the working electrode, a carbon rod as the counter electrode, and Hg / Hg2SO4 as the reference electrode. The electrocatalytic hydrogen evolution performance (LSV) test was carried out in 0.5MH2SO4 solution (as the electrolyte). The scanning speed of the LSV test was 2mV·s -1 , the experimental test temperature is 22±2℃. For specific results, see Figure 6-8 .
[0082] Depend on Figure 6 a and Figure 6 b The results show that the acidic hydrogen evolution performance of the Mo2C / MoO2 substrate material containing heterojunctions is greatly improved after loading the PtNi alloy. This is because the introduction of the Ni source helps to regulate the electronic structure of Pt and form a Pt electron-rich region, thereby effectively improving the catalytic hydrogen evolution activity. In addition, after the PtNi alloy is loaded, the interaction between it and the Mo2C / MoO2 substrate material containing heterojunctions as a carrier helps to improve the long-term stability under acidic conditions. Among them, reaching 10mA cm -2 The overpotential of the current density decreased from 136mV to 67mV; the Tafel slope decreased from 145mV dec -1 Reduced to 22mV dec -1 .
[0083] Depend on Figure 7From the results, we can see that Ni-Mo2C / MoO2 has poor hydrogen evolution performance, followed by Pt-Mo2C / MoO2, and PtNi-Mo2C / MoO2 has the best hydrogen evolution performance. This is attributed to the strong electronic interaction between Pt and Mo. The addition of Ni can optimize the electronic structure of Pt and form an electron-rich region of Pt, which is conducive to the reduction of protons and the desorption of intermediates. The strong interaction between electrons and the synergistic effect of rich Pt electrons make PtNi-Mo2C have ultra-high mass activity and excellent long-term HER stability. This result shows that constructing PtNi alloy is the optimal hydrogen evolution strategy. Figure 7 b The results show that at 1A cm -2 Under a high current density, the stability test was carried out for 650 hours and the stability was still high, which indicates that the PtNi-Mo2C / MoO2 composite material prepared by the present invention has a long-term stable hydrogen evolution performance as a catalyst.
[0084] Depend on Figure 8 a The results show that the PtNi-Mo2C / MoO2 composite material prepared by the present invention can achieve the same catalytic performance as commercial Pt / C; Figure 8 b The results show that, when converted into mass activity, the mass activity of the PtNi-Mo2C / MoO2 composite material is much better than that of commercial Pt / C. Therefore, the platinum-supported molybdenum carbide / molybdenum dioxide nanocomposite provided by the present invention can be used as a hydrogen evolution catalyst with excellent performance in the electrolysis of water to produce hydrogen.
[0085] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.
Claims
1. A method for preparing a platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material, characterized in that: The following steps are involved: S1. Preparation of Mo2C / MoO2 substrate material containing heterojunction: S11, dissolving the metal molybdenum salt and the ligand in deionized water, adjusting the pH to 4-5, reacting at a certain temperature, purifying, and drying; S12, subjecting the dried reaction product to pyrolysis treatment to obtain a Mo2C / MoO2 substrate material containing a heterojunction; S2. Preparation of platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite materials: The Mo2C / MoO2 substrate material containing the heterojunction is dissolved in water, and a platinum source, a nickel source, a surfactant, a reducing solvent and an acid are added, mixed and reacted to obtain a platinum-nickel-loaded molybdenum carbide / molybdenum dioxide nanocomposite material.
2. The method for preparing the platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material according to claim 1, characterized in that: In step S11, the ratio of the amount of the metal molybdenum salt, the complexing agent and the deionized water is 2-5 g: 1-3 mL: 25-40 mL.
3. The method for preparing the platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material according to claim 1, characterized in that: In step S11, the reaction temperature is 30-80°C, the reaction time is 2-3h; and the drying temperature is 30-100°C.
4. The method for preparing the platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material according to claim 1, characterized in that: In step S12, the pyrolysis treatment is performed at 600-650°C and the pyrolysis time is 1-2 hours.
5. The method for preparing the platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material according to claim 1, characterized in that: In step S2, the reaction temperature is 50-90° C., and the reaction time is 5-10 h.
6. The method for preparing the platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material according to claim 1, characterized in that: In step S2, the platinum source, nickel source, surfactant, Mo2C / MoO2 substrate material containing a heterojunction, reducing solvent, acid and deionized water are used in a ratio of 5-35 mg: 5-35 mg; 30-50 mg: 100 mg: 10 μL: 25 μL: 20 mL.
7. The method for preparing the platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material according to claim 1, characterized in that: In step S1, the metal molybdenum salt is ammonium heptamolybdate tetrahydrate; the complexing agent is ethylenediamine; and the acid for adjusting pH is any one of dilute hydrochloric acid, dilute sulfuric acid, and acetic acid.
8. The method for preparing the platinum-nickel loaded molybdenum carbide / molybdenum dioxide nanocomposite material according to claim 1, characterized in that: In step S2, the platinum source is potassium chloroplatinate; the acid is hydrochloric acid with a concentration of 6 to 10 mol / L; the nickel source is nickel chloride hexahydrate; the surfactant is polyoxyethylene polyoxypropylene ether; and the reducing solvent is ethanol.
9. A platinum-nickel supported molybdenum carbide / molybdenum dioxide nanocomposite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the platinum-nickel supported molybdenum carbide / molybdenum dioxide nanocomposite material as claimed in claim 9 as an electrocatalyst in hydrogen production by electrolysis of water.
Citation Information
Patent Citations
Platinum-based / molybdenum-based compound-carbon catalyst and preparation method therefor
CN105552390A
Platinum-loaded molybdenum dioxide hybrid nano material and preparation method and electro-catalysis application thereof
CN113430568A
Cited By
Alkaline hydrogen evolution catalyst for hydrogen production through water electrolysis and preparation method of alkaline hydrogen evolution catalyst
CN120844141A